Tempering Grief through the Victorian Home’s Furniture and Objects: The Emergence of Spiritual Comfort - Galvin, Vanessa (Interior Design/Interior Architecture Educators Association, 2022)
This paper describes the emergence of spiritual comfort in the home by exploring how Victorian Spiritualists formed an intimate and meaningful connection to the home’s furniture and contents. Through their contentious beliefs and practices, believers of spiritualism transformed their living rooms into fantasy realms where the souls of their deceased loved ones continued to dwell. Through otherworldly interactions the bereaved found solace in the place they experienced grief most acutely: the home. As a part of the discussion, I undertake an analysis of Morrel Theobald’s book, Spirit Workers in the Home Circle, (1887). In addition, I consider how Theobald used his manuscript to present ‘scientific proof’ of the supernaturalist occurrences in his home, and a public platform to authenticate spiritualism as a ‘truth claim’. His primary motive in Spirit Workers was for spiritualism to be accepted as a reasonable way of life for the greater good of all individuals. My analysis involves a discussion of the text through Foucault’s term parrhesia which is a ‘verbal activity’ where the speaker ‘risks his life’ to articulate his personal relation to the truth. I describe how Theobald jeopardised his reputation as a rational, reputable human being to promote his spiritualist agenda and his interior’s role in proving spiritualism to be a legitimate way of life.